Análisis de las políticas comerciales en torno a los procesos de importación de arroz en Colombia: Mitos y Realidades (2022)
This document describes and analyzes the conditions around the economic and political conditions of the Colombian rice sector, in which it is found that there are multiple deficiencies in the development of the sector where investment in machinery and technologies has been handled in a not so optimal way, in which the ineffectiveness of the Colombian State to the territories and rice farmers predominates, which have high challenges to face such as imports, smuggling and the lack of commercial and economic policies that favor the sector. The main objective of this research was aimed at analyzing the conditions of the rice sector in Colombia during the last years, finding that there has been a growth and strong obstacles whose causes are diverse and that here are mentioned as the commercial relations of FTA between Colombia and the United States, or the relationship with the CAN.